The Role of Ecosystem Services in Holistic Conservation within Protected Areas: A Case Study of the Song Thanh National Park, Vietnam - Nghiem, Tuyen; Saksena , Sumeet; Ha , Hue T.; Dao , Truong; Le, Toan; Vu , Huong D.; Nguyen, Dien; Hoc , Truong Q. (Forest and Society, 2025)
Vietnam has made a strong commitment to biodiversity conservation, as evidenced by its extensive network of protected areas. However, environmental issues persist in protected areas. Often, the resulting violence complicates the situation, making it more challenging to analyze and manage. We studied the perceptions of people in the buffer zone of the Song Thanh National Park, Quang Nam province, regarding the current status of ecosystem services (ES), the importance of ecosystem services, their changes over time, and people's participation in protecting ecosystem services. We employed a mixed-methods approach, combining qualitative and quantitative data. We conducted semi-structured interviews, focus group discussions, key informant interviews, and household surveys. We found that local communities were aware of the current status of ecosystem services they used and the importance of prominent selected services, such as swidden agriculture and water resources, in their lives. The study also showed how people perceived the improvement of regulatory services since the establishment of the national park, while the extraction of forest ecosystem services led to legal violations. People's dependence on the provisioning services provided by protected areas often leads to environmental conflicts in their management. This study provides strong evidence that conservation is essential; however, an ES approach is needed to manage protected areas effectively to meet conservation objectives.